TINJAUAN KLASTER HAK SIPIL DAN KEBEBASAN ANAK DALAM MEWUJUDKAN KOTA LAYAK ANAK DI KOTA SERANG - Arenawati Arenawati; Listyaningsih Listyaningsih (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
Children as the next generation must get the rights of certainty, development and growth . Government must have effort to protect their right was outlined in the child protection policies, programs and activities to ensure the fulfillment of children's rights, so that children can live, grow, develop and participate optimally in accordance with human dignity, as well as protection from violence and discrimination. One of the policies to guarantee the rights of the child is Kota Layak Anak Programm. One cluster of this program is The ciivil rights and freedoms. The Civil rights and freedom includes the right to identity, identity protection, the right of expression and speech, the right of thought, conscience and religion, freedom of association and peaceful assembly, the right to protection of private life, the right of access and adequate information, the right of free of punishment and torture, this study aims to determine how cluster civil rights and child development in the development of the children friendly city in Serang. The method used is qualitative ,data collection techniques of documentation and interviews. The main source of data is secondary data. The results showed that the achievement on the cluster of civil rights and freedoms of children still less, some local district children civil right owner still less than fifty percent, we can’t find children forum in every vilage, free playground is limited . Preparing to developing Kota Layak Anak in Serang City actually only make a policy , not yet planning action. Our recommendations are: the first necessary to set up groups of children to support the creativity of children, the second to increas the function of children communication forum .Keywords: Children, civil rights, freedom